(3MRH GdCfSs - (3Ydj Hf YHO Gddg GdTGPdj, fhQ GdOjf CHj GdMSf,J (B656 (3g` s
(3ChdgG (B:s
(3CYhP HGddg ef GdTjWGf GdQLje HSe Gddg GdQMef GdQMje GdMeO ddg QH GdYGdejf GdQMef GdQMje eGdc jhe GdOjf QHfG dBJfG ef dOfc QMeI hgF dfG ef CeQfG QTOkG s
(3BNQgG (B:s
(3Gddge hUd Ydi LHQjd hejcGFjd hGSQGajd hYRQGFd hYdi MedI GdYQT hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B661s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9321) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs